2012
DOI: 10.1029/2012jc008078
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of two different satellite‐derived precipitation products in relation to simulation of sea surface salinity in the tropical Indian Ocean

Abstract: The focus of the study is on the assessment of two different satellite-derived precipitation products in relation to the simulation of sea surface salinity (SSS) in the tropical Indian Ocean by an ocean general circulation model (OGCM). Precipitation derived from the National Centre for Environmental Prediction (NCEP) has also been used as a benchmark. The period of the simulations covers the years 2003-2007. A comparison with Argo floats suggests that both the satellite products are more effective than NCEP p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…One way is to replace the numerical weather prediction (NWP) model generated precipitation with more realistic satellite-derived precipitation [Sharma et al, 2012]. One way is to replace the numerical weather prediction (NWP) model generated precipitation with more realistic satellite-derived precipitation [Sharma et al, 2012].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One way is to replace the numerical weather prediction (NWP) model generated precipitation with more realistic satellite-derived precipitation [Sharma et al, 2012]. One way is to replace the numerical weather prediction (NWP) model generated precipitation with more realistic satellite-derived precipitation [Sharma et al, 2012].…”
Section: Introductionmentioning
confidence: 99%
“…In the Indian Ocean, there is an independently coupled ocean-atmosphere mode, known as Indian Ocean Dipole or IOD in short [Saji et al, 1999]. SSS plays a crucial role in this coupling [Thompson et al, 2006;Sharma et al, 2007Sharma et al, , 2012. Further, it has been shown that SSS in the southeastern Arabian Sea (SEAS) is intimately linked with the onset of summer monsoon [Masson et al, 2005].…”
Section: Introductionmentioning
confidence: 99%
“…As clear from the title of our study and also from what has been stated in the Introduction, the major aim of our study is the assessment of the impact of precipitation on SST and sea level, since a thorough study of the impact of satellite-derived precipitation on SSS has been conducted earlier (Sharma et al 2012). Moreover, because of the availability of satellite-derived SSS from Aquarius over large areas of global oceans, it is interesting to see how the model forced by satellite-derived precipitation is performing in terms of SSS simulation.…”
Section: Comparison Of Precipitation Forcings and Simulated Sss With mentioning
confidence: 98%
“…Hence, it is imperative to study the impact of satellite-derived products on ocean general circulation models (OGCMs). Very recently such an impact study has been carried out using an OGCM (Sharma et al 2012), but the analysis was restricted to the tropical Indian Ocean only and the emphasis was only on SSS variability.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, however, this remains still an elusive goal primarily because of the imperfect knowledge of the evaporation minus precipitation (E-P) budget [Durand et al, 2002]. Although it has been shown recently [Sharma et al, 2012] that satellite-derived precipitation is better suited than numerical weather prediction (NWP) model generated precipitation for obtaining more realistic SSS simulation, the simulated SSS has not yet reached the desired level of accuracy. Other makeshift solution is, of course inclusion of ad hoc correction term in the model equation for salinity [Durand et al, 2003].…”
Section: Introductionmentioning
confidence: 99%